2021
DOI: 10.1007/s10212-021-00535-3
|View full text |Cite|
|
Sign up to set email alerts
|

The links between students’ relationships with teachers, likeability among peers, and bullying victimization: the intervening role of teacher responsiveness

Abstract: Highly responsive teachers tend to foster behaviors that are low in conflict and high in prosociality, among their students, leading to a positive classroom climate and to a decrease in bullying victimization. However, little is known about the interaction between teacher responsiveness and both student–teacher, and student–student relationship characteristics, in influencing students’ bullying victimization at school. Here, we examined student–teacher relationship quality and students’ likeability among peers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 60 publications
0
14
0
1
Order By: Relevance
“…However, it is possible that the deficits in social skills often exhibited by adolescents with SMA may also recur in the online environment and negatively affect the quality of interactions online, which impacts their feelings of loneliness and psychological distress (Dredge & Schreurs, 2020). Furthermore, constant use of social media may increase the risk of victimization (Longobardi et al, 2020(Longobardi et al, , 2021(Longobardi et al, , 2022 and fuel feelings of frustration and envy through constant social comparisons (Radovic et al, 2017). In this sense, the online environment may increase psychological stress and frustration among adolescents and eventually contributes to an increased risk of aggressive behaviors.…”
Section: Social Media Addiction and Aggressive Behaviors In Adolescentsmentioning
confidence: 99%
“…However, it is possible that the deficits in social skills often exhibited by adolescents with SMA may also recur in the online environment and negatively affect the quality of interactions online, which impacts their feelings of loneliness and psychological distress (Dredge & Schreurs, 2020). Furthermore, constant use of social media may increase the risk of victimization (Longobardi et al, 2020(Longobardi et al, , 2021(Longobardi et al, , 2022 and fuel feelings of frustration and envy through constant social comparisons (Radovic et al, 2017). In this sense, the online environment may increase psychological stress and frustration among adolescents and eventually contributes to an increased risk of aggressive behaviors.…”
Section: Social Media Addiction and Aggressive Behaviors In Adolescentsmentioning
confidence: 99%
“…For example, Serdiouk et al (2016) used data from 1700 elementary school students in the United States and found that children with more teacher-student closeness reported lower levels of peer victimization. Based on a sample of 386 early-adolescent students from Italy, Longobardi et al (2021) found that teacher-student conflict was associated with an increased risk of peer victimization. Therefore, the direction of the associations between teacher-student relationships and peer victimization in China is similar to that in the West.…”
Section: Associations Between Teacher-student Relationships and Peer ...mentioning
confidence: 99%
“…According to Pianta and Allen (2008), a positive teacher-student relationship "is the single most important ingredient in promoting youth development" (24). Research findings showed that teacher-student relationships contribute considerably to students' academic, social, and emotional development during the preschool years (Mashburn et al, 2008;Roorda et al, 2011;Brock and Curby, 2014;Longobardi et al, 2021). Prior research suggest that supportive relationships also influence the students' long-term behavioral outcomes (Hamre and Pianta, 2001;Roorda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%